Ventilator-Associated Pneumonia Prevention - Arnold, Cierra A (URJ-UCCS: Undergraduate Research Journal at UCCS, 2018)
Ventilator-Associated Pneumonia is a common form of hospital acquired pneumonia associated with mechanically ventilated patients. Evidence-based research revealed that some interventions performed by the health care team decrease the occurrence of Ventilator-Associated Pneumonia. Many hospitals have taken the initiative to incorporate universal interventions, but new evidence suggests there are more effective ways to implement traditional interventions to improve patient outcomes. Concepts that will be discussed are: a bundle checklist, identifying at-risk patients, head of bed elevation, oral care, and proper suctioning. Researchers found modifications to traditional interventions to improve patient outcomes.